Prevalence of Anxiety and Depression among Parents of Children with Cancer-A Preliminary Study - Anna Lewandowska; Tomasz Lewandowski; Anna Bartosiewicz; Katalin Papp; Dana Zrubcová; Mária Šupínová; Aleksandra Stryjkowska-Góra; Barbara Laskowska; Gabriela Joniec; Serap Ejder Apay (MDPI AG, 2024)
Background: A child's cancer is a highly stressful experience for the entire family. Childhood cancer disrupts family functioning and is one of the most stressful and challenging events parents face, often beyond their control. Parents play a crucial role in providing emotional support to children throughout their illness, and their ability to cope can help reduce the child's negative emotions. The aim of this study was to assess the prevalence of anxiety and depression among parents of children with cancer. Methods: This cross-sectional study followed the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines and included parents of children undergoing cancer treatment. Convenience sampling was used. The Beck Depression Inventory and the Hospital Anxiety and Depression Scale were utilized to assess the parents. Results: This study included 270 participants (73% women, 27% men) with children at an average age of 8.75 ± 4.82 years. Diagnoses included leukemia (53%), lymphoma (29%), and other cancers. On the Beck Depression Inventory, 33% of parents were mildly depressed, 12% moderately depressed, and 32% severely depressed, with an average score of 20.63 ± 12.39 points. The HADS-M scale indicated anxiety at 48.43 ± 20.78%, depression at 45.01 ± 22.8%, and aggression at 54.72 ± 28.71%. Conclusions: Most parents of children with cancer have symptoms of depression and anxiety, which are influenced by the duration of the child's illness. A strong correlation was observed between the level of anxiety and the tendency for depression.